2017
DOI: 10.18632/oncotarget.22970
|View full text |Cite
|
Sign up to set email alerts
|

MAEL contributes to gastric cancer progression by promoting ILKAP degradation

Abstract: The cancer-testis gene MAEL is involved in the development and progression of bladder, liver and colorectal cancers. However, its role in other cancers is unclear. By systematically analyzing transcriptomics and genomics data from various cancer databases, we identified that the MAEL gene is aberrantly elevated in gastric cancer (GC) tissues and that its expression is strongly negatively correlated with DNA methylation (Pearson's correlation coefficient = −0.675). Survival analysis revealed that MAEL expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The target sequences of ZCCHC10 shRNAs are listed in Supplementary Table S3. Infection and selection for stable cell lines were performed as described previously 20 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The target sequences of ZCCHC10 shRNAs are listed in Supplementary Table S3. Infection and selection for stable cell lines were performed as described previously 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Co-IP experiments were performed using endogenous proteins in Beas-2b and overexpressed proteins in Hek293 cells as previously described 18,20 . For analyzing the effect of ZCCHC10 on the interaction between p53 and MDM2, Hek293 cells were co-transfected with 3 μg of HA-p53 plasmid, 3 μg of Myc-MDM2C464A plasmid and an increasing amount (0, 3, 6, 9 μg) of EGFP-ZCCHC10 plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAELSTROM protein (MAEL) is a novel diagnostic biomarker for gastric cancer. A previous study revealed that the function of MAEL is closely linked to epithelialmesenchymal transition (EMT) and stem cell properties (Zhang et al, 2017). Lck Interacting Transmembrane Adaptor 1 (LIME1) is a transmembrane adaptor involved in the activation of BCR (B-cell antigen receptor)-mediated signaling via interaction with Lck and Lyn (Hořejšì, 2004).…”
Section: Discussionmentioning
confidence: 99%